2015
DOI: 10.1063/1.4921538
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and magnetic properties of off-stoichiometric Co2MnβSi/MgO interfaces studied by x-ray magnetic circular dichroism

Abstract: We have studied the electronic and magnetic states of Co and Mn atoms at the interface of the Co2Mn β Si (CMS)/MgO (β=0.69, 0.99, 1.15 and 1.29) magnetic tunnel junction (MTJ) by means of x-ray magnetic circular dichroism. In particular, the Mn composition (β) dependences of the Mn and Co magnetic moments were investigated. The experimental spin magnetic moments of Mn, mspin(Mn), derived from XMCD weakly decreased with increasing Mn composition β in going from Mn-deficient to Mn-rich CMS films. This behavior w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The CMFS thin film was deposited at RT using radiofrequency magnetron cosputtering from three targets, i.e., nearly stoichiometric CMS, Mn, and Fe, in an ultrahigh vacuum chamber (that has a base pressure of 6 × 10 [47], electronic, and magnetic properties [33][34][35][36][37][38][48][49][50]. The MgO buffer and barrier were deposited by electron beam evaporation in the same chamber at 400°C and RT, respectively.…”
Section: A Experimental Methodsmentioning
confidence: 99%
“…The CMFS thin film was deposited at RT using radiofrequency magnetron cosputtering from three targets, i.e., nearly stoichiometric CMS, Mn, and Fe, in an ultrahigh vacuum chamber (that has a base pressure of 6 × 10 [47], electronic, and magnetic properties [33][34][35][36][37][38][48][49][50]. The MgO buffer and barrier were deposited by electron beam evaporation in the same chamber at 400°C and RT, respectively.…”
Section: A Experimental Methodsmentioning
confidence: 99%
“…Picozzi et al predicted from first principles that half-metallicity in CMS and Co 2 MnGe (CMG) is lost for Co Mn antisites, where a Mn site is replaced by a Co atom, because of the appearance of minority-spin in gap states near E F , while half-metallicity is retained for Mn Co antisites, where a Co site is replaced by a Mn atom [33]. The effect of off-stoichiometry on the half-metallicity of CMS and CMG has been systematically investigated recently using various experimental approaches, including the tunneling magnetoresistance (TMR) ratios of MTJs [9][10][11][12], the saturation magnetization per formula unit of thin films [12], the surface spin polarization [42], the magnetic states as investigated by x-ray absorption spectroscopy and x-ray magnetic circular dichroism [43][44][45], and the electronic states as investigated through spin-resolved low-energy and hard x-ray photoelectron spectroscopy [46][47][48]. These experimental studies, along with first-principles calculations, demonstrated that Co Mn antisites induced by a Mn-deficient composition (the Mn composition α < 2 − β in the composition expression of Co 2 Mn α Si β ) is detrimental to the half-metallicity of CMS.…”
Section: Introductionmentioning
confidence: 99%
“…Figure b refers to a gradual decrease in the XMCD signal with the increasing thickness of the SiO 2 coating due to the nonmagnetic SiO 2 coating at the surface hindering the proper signal of the magnetic core. In the present work, the XMCD measurements were carried out through a bulk-sensitive total fluorescence yield (TFY) mode that has a long probing depth of ∼100 nm , and probe the bulk spin and orbital magnetic moments of NPs at 300 K. The surface-sensitive total electron yield (TEY) mode has a probing depth of ∼10 nm, more active at the surface edge. , This experimental specification in the TFY mode is different from the TEY mode of XMCD as also reported by Amemiya et al …”
Section: Resultsmentioning
confidence: 65%